Gaya Kepemimpinan Mikromanajemen dan Kinerja Karyawan Generasi Z di Indonesia - Andriyani, Yunita; Wulandari, Jeni; Saptiani, Fenny; Rifa'i, Ahmad (Universitas Diponegoro, 2024)
Currently, leadership has been recognized as an urgent and important issue for companies to face in the generation Z era, which increasingly dominates the job market. Generation Z expects leaders who give them flexibility, responsibility, and space in the work process. However, the leadership approach that is often found emphasizes a micromanager style, which often lacks trust in employees' abilities to complete tasks independently and delegates responsibility only in small portions. This causes Generation Z's low level of engagement in the workplace. This research aims to analyse the influence of micromanagement leadership style on the performance of generation Z employees. The research sample consisted of 400 respondents from generation Z employees in Indonesia who were determined by non-probability sampling. Data was collected through questionnaires and analysed using linear regression analysis. The research results show that the higher the application of micromanagement leadership styles, such as excessive interference, tight supervision, excessive control, limiting authority, and giving excessive attention, the greater the impact on decreasing the performance of generation Z employees. Characteristics of generation Z tend to like freedom, creativity, and independence, making them feel constrained and less motivated when working under an overly controlling leadership style. These findings provide implications for the importance of considering generational differences in leadership practices.Saat ini, kepemimpinan telah direkognisi sebagai masalah mendesak dan penting untuk dihadapi perusahaan di era generasi Z yang semakin mendominasi pasar kerja. Generasi Z mengharapkan pemimpin yang memberikan mereka fleksibilitas, tanggung jawab, dan ruang dalam proses bekerja. Namun, pendekatan kepemimpinan yang sering dijumpai menekankan pada gaya mikromanajer yang seringkali kurang mempercayai kemampuan karyawan dalam menyelesaikan tugas secara mandiri dan mendelegasikan tanggung jawab hanya dalam porsi yang kecil. Hal ini menyebabkan rendahnya tingkat keterikatan generasi Z di tempat kerja. Penelitian ini bertujuan untuk menganalisis pengaruh gaya kepemimpinan mikromanajemen terhadap kinerja karyawan generasi Z. Sampel penelitian berjumlah 400 responden karyawan generasi Z di Indonesia yang ditentukan secara non-probabilitas. Data dikumpulkan melalui kuesioner dan dianalisis menggunakan analisis regresi linier. Hasil penelitian menunjukkan bahwa semakin tinggi penerapan gaya kepemimpinan mikromanajemen, seperti campur tangan berlebihan, pengawasan ketat, pengontrolan berlebihan, membatasi kewenangan, dan memberi perhatian berlebihan, maka akan berdampak pada penurunan kinerja karyawan generasi Z. Karakteristik generasi Z yang cenderung menyukai kebebasan, kreativitas, dan kemandirian, membuat mereka merasa terkekang dan kurang termotivasi saat bekerja di bawah gaya kepemimpinan yang bersifat mengontrol secara berlebihan. Temuan ini memberikan implikasi pentingnya mempertimbangkan perbedaan generasi dalam praktik kepemimpinan.